KEBUTUHAN SEKOLAH SUNGAI DALAM UPAYA PENINGKATAN KUALITAS LAYANAN DI MASYARAKAT - Akhmad Rofiq; Entoh Tohani (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2021)
This study aims to describe the needs for Sekolah Sungai development in the communities around the Winongo River. As an institution engaged in the social sector, Sekolah Sungai needs various developments to increase the existence and usefulness of institutions in the communities around the Winongo river in an effort to reduce disaster risk. The research method used in this research is descriptive qualitative, using data collection techniques through interviews, observation, and documentation. The results of the study show that there are several development needs that must be followed up by Sekolah Sungai in order to increase the usefulness of the institution. The Sekolah Sungai development needs include the following: 1) development of an innovative Sekolah Sungai program; 2) Development of learning methods; 3) improving the quality of Sekolah Sungai management resources; 4) procurement of facilities and infrastructure; 5) increasing public awareneSekolah Sungai; and 6) partnerships. Without any development efforts carried out, it will certainly cause Sekolah Sungai to have no power in educating the public regarding disaster risk reduction and increasing public awareneSekolah Sungai of river management. Meanwhile, with the development carried out, it will have a good impact on the sustainability of Sekolah Sungai in the community which in the end can be an alternative for the community to become a vehicle for learning related to disaster mitigation and river management.